2020
DOI: 10.4314/ahs.v20i4.8
|View full text |Cite
|
Sign up to set email alerts
|

VMMC clients’ perception of increased risk of HIV infection, circumcision preferred choice of method, providers’ socio-demographics and mode of service delivery

Abstract: Introduction: Voluntary medical male circumcision (VMMC) is a scientifically proven HIV prevention intervention. Uganda, like many countries has been implementing VMMC for over 10 years but uptake is still low especially in northern Uganda. To attain 80% needed for public health impact, scale-up was recommended with many innovations implemented with sub-optimal results. This study therefore wanted to find out some of the correlates of VMMC uptake in Gulu district, northern Uganda. Methods: Two studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In an attempt to meet the world's commitment to ending the AIDS epidemic by 2030 [ 2 ], the WHO recommended SMC as one of the HIV prevention measures. The Ugandan government expected to have circumcised 6.9 million men aged 10-49 by 2020, though by 2016, only 2.5 million men had circumcised and there has never been a great mass safe male circumcision as it was in 2014 [ 3 ]. Recent studies have shown that there is a very high increase in the prevalence of HIV among the youth aged 20–24 years in Uganda standing at 10.8% [ 4 ], almost doubling the national prevalence of HIV in Uganda at 6.2% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to meet the world's commitment to ending the AIDS epidemic by 2030 [ 2 ], the WHO recommended SMC as one of the HIV prevention measures. The Ugandan government expected to have circumcised 6.9 million men aged 10-49 by 2020, though by 2016, only 2.5 million men had circumcised and there has never been a great mass safe male circumcision as it was in 2014 [ 3 ]. Recent studies have shown that there is a very high increase in the prevalence of HIV among the youth aged 20–24 years in Uganda standing at 10.8% [ 4 ], almost doubling the national prevalence of HIV in Uganda at 6.2% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a high HIV prevalence in the Northern Uganda region with a 7.2% prevalence of HIV compared to the national prevalence of 6.2% [ 5 ]. There is also a growing number of males opting out of circumcision since 2016 up to today [ 3 ]; however, younger males remain reluctant to undertake this voluntary initiative. This coupled with the limited numbers of young people undertaking HIV testing and other sexual and reproductive health services in Northern Uganda of about 43% and 42%, respectively, poses a significant challenge in the fight against HIV/AIDS and other sexually transmitted infections [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then follows the attempt by the HIV community to understand the ramifications of the HIV pandemic in Africa despite having lived with it for almost 4 decades now! Hence we have papers on: outcomes on PLHIV in Kenya 4 CD4 counts, 5 VMMC and HIV risk in Uganda, 6 HIV and fungal infection 7 , HIV in Wuhan China 8 that city that gave Covid-19 to the world; and HIV and primary school teachers. 9 Then comes dengue, 10 hepatitis B and osteoporosis, 11 TB, 12 H.pylori , 13 MDR Staph.…”
mentioning
confidence: 99%